Planejamento, síntese e avaliação farmacológica de compostos híbridos potencialmente ativos para o tratamento da anemia falciforme - Santos, Jean L. [UNESP] (Elsevier, 2010)
Sickle cell disease (SCD) is a hereditary hemolytic anemia caused by the inheritance of one S hemoglobin gene from each ancestor. Patients with SCD present increased circulating levels of cytokines, including TNF-alpha (TNF-α). Hydroxyurea (HU) is the available therapeutically strategy for treatment; it acts as a source of nitric oxide and benefits patients by increasing the levels of fetal hemoglobin (HbF). Thus, within one research line that aims at finding new drugs, a series of compounds with TNF-α inhibition and nitric oxide donation properties have been synthesized in order to explore possible synergism of actions beneficial in the treatment of the disease. Six compounds were synthesized: five derivatives of organic nitrates and one of sulfonamide. The compounds, (1,3-dioxo-1,3-dihydro-2Hisoindol-2-yl) methyl nitrate (compound I); (1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl) ethyl nitrate (compound II); 3-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl) benzyl nitrate (compound III);4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)-N-hydroxybenzenesulfonamide (compound IV); 4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl) benzyl nitrate (compound V) and 2-[4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl) phenyl]ethyl nitrate (compound VI), were synthesized using linear synthetic methodology, with excellent overall yields. All compounds showed anti-inflammatory and analgesic effects with a reduction in 43%-65% of ear edema in mice and a reduction of 25%-42% of writhing induced by acetic acid. All compounds showed comparable reductions in the leukocyte infiltration capacity and ability to generate nitric oxide. The aryl compounds (III, IV and V) presented less mutagenic activity compared to compounds I, II and VI according to the salmonella mutagenicity assay (Ames test). Compounds IV and VI showed activity in K562 culture cells, with increases in gamma globin gene expression to levels higher than with hydroxyurea suggesting a potential to increase fetal hemoglobin. This data set characterizes new potentially useful drug candidates for the treatment of symptoms of sickle cell anemia.
Design, synthesis and pharmacological evaluation of hybrid compounds that are potentially active in the treatment of sickle cell disease
Keywords: Anemia, sickle cell; Fetal hemoglobin; Hemoglobinopathies